Let $\gamma(s)$ be a smooth curve in $\mathbb{R}^3$ parametrized by arclength. Supposed that for some function $f(s)$, $\gamma''(s) = f(s)\gamma(s)$. What can you deduce about $f(s)$ and $\gamma(s)$?

Hint: Consider taking dot product by the vector $\gamma' = T$ and interpret the outcome.

We are having difficulty interpreting the outcome of this exercise. We did the following:

$\gamma'\cdot\gamma''=T.\kappa N=(T.N)\kappa=0$, since we are in the $\{T,N,B\}$ frame. From this we have that $\gamma'\cdot f\gamma=0$. Hence $\gamma'$ is perpendicular to $f\gamma$. Would this be sufficient or is there any other interpretation we are overlooking?

  • $\begingroup$ Of course $\gamma' \perp f\gamma$. We have $\gamma' = {\bf T}$ and $f\gamma = \gamma'' = {\bf T}' = \kappa {\bf N}$. So all you're saying is ${\bf T} \perp {\bf N}.$ $\endgroup$ – Fly by Night Nov 5 '12 at 18:07

First, let us consider $\gamma''.$ We have $\gamma' = {\bf T}$ and so $\gamma'' = {\bf T}' = \kappa{\bf N}.$ If $\gamma'' = f\gamma$ then it tells us that $\gamma \propto {\bf N}$ and so both the osculating and the normal planes pass through the origin.

Next, let us differentiate the expression $\gamma'' = f\gamma.$ We get $\gamma''' = f'\gamma + f \gamma' = f'\gamma + f{\bf T}$. Consider the left hand side, we know that $\gamma' = {\bf T}$ and so $\gamma'' = {\bf T}' = \kappa{\bf N}$, and finally

$$\gamma''' = (\kappa{\bf N})' = \kappa'{\bf N} + \kappa{\bf N}' = \kappa'{\bf N} + \kappa(\tau{\bf B}-\kappa{\bf T}) = -\kappa^2{\bf T} + \kappa'{\bf N} + \kappa\tau{\bf B} \, . $$

Thus, $\gamma''' = f'\gamma + f{\bf T}$ implies $f'\gamma + f{\bf T} = -\kappa^2{\bf T} + \kappa'{\bf N} + \kappa\tau{\bf B}.$ We have already seen that $\gamma \propto {\bf N}$. Let us write $\gamma = \alpha{\bf N}.$ Fianlly we get:

$$\alpha f'{\bf N} + f{\bf T} = -\kappa^2{\bf T} + \kappa'{\bf N} + \kappa\tau{\bf B} \, . $$

Since ${\bf T},$ ${\bf N}$ and ${\bf B}$ are linearly independent it follows that $f=-\kappa^2$, $\alpha f' = \kappa'$ and $\kappa\tau=0.$

One possibility is that $\kappa \equiv 0$.

Let us assume $\kappa \not\equiv 0$. It follows from $\kappa\tau = 0$ that $\tau \equiv 0,$ and $f = - \kappa^2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.